“THE IMPACT OF ENGLISH ON STUDENTS’ CAREER DEVELOPMENT” (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This paper explores the influence of English proficiency on students’ career development in Uzbekistan. As the demand for international communication and global workforce participation continues to rise, English has become a decisive factor in determining students’ future opportunities. The study is based on classroom observations in both rural and urban educational contexts, as well as project-based experiences at the university level. The findings reveal that students with strong English skills have greater access to scholarships, international exchange programs, and competitive job markets. Furthermore, the possession of English certificates such as IELTS or CEFR not only enhances academic mobility but also brings financial benefits through salary increments and additional recognition in the teaching profession. Special attention is given to the perspectives of female students, who emphasized the importance of English as a gateway to international grants and empowerment. The study concludes that English is not merely a subject in education but a key driver of career development, confidence building, and global integration.